Sedimentation from flocculated suspensions in the presence of settling‐driven gravitational interface instabilities. Issue 9 (23rd September 2015) - Rouhnia, Mohamad; Strom, Kyle
Abstract We experimentally examine sedimentation from a freshwater suspension of clay flocs overlying saltwater in the presence of gravitational instabilities. The study seeks to determine: (1) if flocculation hampers or alters interface instability formation; (2) how the removal rates of sediment from the buoyant layer compare to those predicted by individual floc settling; and (3) whether or not it is possible to develop a model for effective settling velocity. The experiments were conducted in a tank at isothermal conditions. All experiments were initially stably stratified but later developed instabilities near the interface that grew into downward convecting plumes of fluid and sediment. Throughout, we measured sediment concentration in the upper and lower layers, floc size, and plume descent rates. The data showed that flocculation modifies the mixture settling velocity, and therefore shifts the mode of interface instability from double‐diffusive (what one would expect from unflocculated clay) to settling‐driven leaking and Rayleigh‐Taylor instability formation. Removal rates of sediment from the upper layer in the presence of these instabilities were on the same order of magnitude as those predicted by individual floc settling. However, removal rates were found to better correlate with the speed of the interface plumes. A simple force‐balance model was found to be capable of reasonably describing plume velocity based on concentration in the buoyant layer. This relation, coupled with a critical Grashof number and geometry relations, allowed us to develop a model for the effective settling velocity of the mixture based solely on integral values of the upper layer.